Chronic Encapsulated Expanding Hematoma After Stereotactic Radiosurgery of Intracranial Arteriovenous Malformation. (16th November 2020) - Abou-Al-Shaar, Hussam; Faramand, Andrew M; Zhang, Xiaoran; Algattas, Hanna; Lunsford, L. Dade
Abstract: INTRODUCTION: Cerebral arteriovenous malformations (AVM) are rare cerebral vascular lesions associated with high morbidity from hemorrhage and rupture with an estimated annual hemorrhage risk of 1.9%-4.5%. Stereotactic radiosurgery is an effective treatment modality that causes vascular thrombosis and occlusion. Few reports have delineated a subgroup of patients who develop chronic encapsulated expanding hematomas despite angiographic evidence of AVM obliteration. METHODS: We performed a retrospective analysis of 1010 AVM patients who underwent Gamma Knife stereotactic radiosurgery between 1988 and 2018 at the University of Pittsburgh Medical Center. Patients' clinical and radiological characteristics and outcomes were recorded and analyzed. RESULTS: Four patients (2 males and 2 females with an average age of 41±14.7 years) developed chronic encapsulated hematoma following stereotactic radiosurgery of intracranial AVM requiring surgical intervention (incidence rate of 0.4%). Initial diagnosis of AVM was made incidentally for 1 patient, secondary to seizures of 2 patients, and as a part of headache work-up for the last patient. Two patients had pre-SRS embolization. Three of the four patients required either additional SRS or surgery to achieve angiographic obliteration of AVM nidus. All of the hematomas were identified on routine follow-up imaging. Time to hematoma discovery from initial SRS was between 8 to 15 years. Average time from hematoma discovery to surgical intervention was 428 days. Most common reason for surgery was new or worsening focal neurologic deficit in the form of aphasia or motor weakness. No intraoperative complications were encountered. One patient developed a post-operative epidural abscess and meningitis requiring wound exploration and lumbar drain placement. At their most recent follow-up, all four patients did well clinically with improvement of focal neurologic deficits. Histopathological examination revealed mixed chronicity hematoma with areas of fibrosed blood vessels. CONCLUSION: Chronic encapsulated expanding hematoma following stereotactic radiosurgery of AVM is an extremely rare complication with an incidence rate of 0.4%. Radical resection of the capsule and residual nidus is recommended for the management of recurrent bleeding and symptomatic control. Knowledge of this rare entity facilitates timely detection and surgical intervention to achieve optimal outcomes.